STRUKTUR DAN KOMPOSISI VEGETASI PADA 3 ZONA ELEVASI YANG BERBEDA DI TAMAN NASIONAL LORE LINDU SULAWESI TENGAH INDONESIA - Pitopang, Ramadanil (Natural Science: Journal of Science and Technology, 2012)
The research on structure and floristic composition of vegetation of  the Lore Lindu National Park has been conducted  from  October to  Desember 2010. The objectives of the research was to study the vegetation potency are included species richness, structure and composition. The Research was located at three locations namely : Bora (elevation  400- 800 m asl), Nokilalaki (elevation 1300-1800 m asl) and Rorekautimbu  (elevation  2100 ? 2600 m asl).  The research was used survey methods through establisment of transect with 20 m in wide.  and in line transect was made nested plot continuously with the size of 20 X 20 m for the observation of trees (dbh> 20 cm), 10 x 10 m for poles, 5 X 5 m and 2 x 2 m to observe the saplings and understorey layer. The result showed that the plant species richness (incl. tree, pole, sapling and seedling and understory plant) in Nokilalaki was higher than  Bora and Rorekautimbu. The diversity index  of Nokilalaki was also higher than Bora and Rorekautimbu. The species composition and structure was indicated the significantly different, where the location I (Bora) was dominated by Dracaena arborea and Tamarindus indica, besides Nokilalaki was dominated by Lithocarpus elegans and Castanopsis accuminatisima (both Fagaceae).  On the other side Rorekautimbu was dominated by Podocarpaceae family such as: Phyllocladus hypophyllus and Dracrycarpus imbricatus. All of research sites studied were very rich with plants are have potency to develop as raw material for  medicine such as Begonia sp, Tasmania piperita and Galbulimima belgraveana. Besides that it was also can be developed as ornamental plant such as: Agalmailla sp (Gesneriaceae), Rhododendrons sp, Vaccinium sp  (both Ericaceae) and several species of pitcher plants  (Nepenthes spp) and soon